Ruskin Library and research center - Ruskin Library (2009)
[Dt.:] Die Ruskin Library in Lancaster hält eine umfassende Sammlung an Manuskripten, Briefen und Büchern von und über den viktorianischen Kunstkritiker John Ruskin (1819-1900). Ein bedeutender Bestand der Bibliothek ist die Whitehouse Collection. Die Ruskin Library stellt über ihre Website eine Bilddatenbank zur Verfügung, welche die Zeichnungen und Aquarelle des Künstlers mit farbigen und vergrößerbaren Abbildungen recherchierbar macht. Auch digitalisierte Originalschriften von Ruskin, wie Modern Painters und Ruskin's Venetian Notebooks (1849-50), sind online frei recherchierbar. - [Engl.:] The Ruskin Library in Lancaster has a large holding of manuscripts, letters, books and drawings by the influential Victorian art critic John Ruskin (1819-1900). Digitalized editions of the art critic's work, such as an electronic edition of Modern Painters and Ruskin's Venetian Notebooks (1849-50) can be studied on the website. A thorough research of primary sources is provided through an index to letters, manuscripts and transcripts. Furthermore, an image database with colour images and object descriptions of drawings and prints by the art critic can be viewed. The website also provides information on exhibitions and other events in the library.